2021
DOI: 10.1080/01902148.2021.1891355
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent hypoxia: Friend or foe on endothelial repair in mouse model

Abstract: Aim of the study: Obstructive sleep apnea, which is characterized by intermittent hypoxia (IH), is a common respiratory disease. The aim of the present study was to explore the relationship between hypoxia and endothelial progenitor cell (EPC) function, and explain the role of IH in endothelial repair. Materials and methods: Peripheral blood mononuclear cells (PBMCs) were isolated from a mouse model of IH. The number of CD133 þ kinase insert domain receptor (KDR) þ , CD133 þ CD34 þ , CD34 þ KDR þ and ALDH low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…Regarding the literature different density gradients were applied for PBMC isolation. For instance, PBMC isolation was published using 1.077 g/cm³ in C57BL/6 mice ( Mendez-David et al, 2013 ; Song et al, 2021 ), whereas 1.084 g/cm³ was used for MRL(-Ipr) mice ( Wang et al, 2018 ). Based on the literature, we tried for murine PBMC isolation a Percoll solution with 1.080 g/cm³ ( Mizobe et al, 1982 ) and compared this to Ficoll™-Plaque PLUS with 1.077 g/cm³.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the literature different density gradients were applied for PBMC isolation. For instance, PBMC isolation was published using 1.077 g/cm³ in C57BL/6 mice ( Mendez-David et al, 2013 ; Song et al, 2021 ), whereas 1.084 g/cm³ was used for MRL(-Ipr) mice ( Wang et al, 2018 ). Based on the literature, we tried for murine PBMC isolation a Percoll solution with 1.080 g/cm³ ( Mizobe et al, 1982 ) and compared this to Ficoll™-Plaque PLUS with 1.077 g/cm³.…”
Section: Discussionmentioning
confidence: 99%
“…Another study also revealed that moderate and severe intermittent hypoxia diminished the mobilization, chemotactic and angiogenetic ability of endothelial progenitor cells. 44 Chronic severe intermittent hypoxia-induced mitochondrial dysfunction could mediate endothelial oxidative stress and apoptosis. 45 , 46 Re-epithelization involving keratinocytes and angiogenesis involving vascular endothelial cells are critical to wound healing.…”
Section: Discussionmentioning
confidence: 99%